EFEKTIVITAS PROGRAM TUKA-TUKU PURBALINGGA DALAM PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KABUPATEN PURBALINGGA - Shafira Nur Isnaeni; Augustin Rina Herawati; Teuku Afrizal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
This research aims to analyze the effectiveness of the “Tuka-Tuku Purbalingga” program in developing MSMEs in Purbalingga district and describe the supporting factors and obstacles that affect the program’s effectiveness. This research uses a model of Sutrisno's effectiveness measurement theory (2007) and a concept by Richard M. Steers (1985) about the supporting factors of effectiveness with qualitative descriptive method. The findings of this research shows that the understanding of the program, the achievement of goals, and real changes in the “Tuka Tuku Purbalingga” program are quite effective in developing MSMEs for business actors. Meanwhile, in the aspect of target accuracy and punctuality, it cannot be considered effective because the target has not yet hit all Purbalingga MSME actors and there is a delay in implementing the program. The supporting factors that help the effectiveness of Tuka Tuku program are characteristic of organization and characteristic of worker, while factors that inhibit program effectiveness include characteristic of environmental and policy & program management practices that are still not optimal. The conclusion of this research is the implementation of the “Tuka Tuku Purbalingga” program is quite effective in developing the MSME actors involved. However, it still needs improvement because there is an obstacle to the program effectiveness. Based on this research, recommendations are given to the implementation of socialization which more intensively, management of Tuka Tuku’s ecommerce which more optimally, and the selection of Tuka Tuku’s outlet location which more strategically.